2001
DOI: 10.4269/ajtmh.2001.64.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic factors and population density on varicella zoster virus epidemiology within a tropical country.

Abstract: Abstract. Blood samples were collected from healthy subjects, aged 9 months-29 years in urban and rural communities from 4 distinct regions in Thailand, to determine the seroprevalence rate of varicella-zoster virus (VZV) antibody and its relationship with demographic, climatic, and socioeconomic factors. The overall seroprevalence rate was 52.8% and increased from 15.5% in the 9-month to 4-year-old group to 75.9% in the 20-29 year-olds. The ageadjusted seroprevalence was significantly higher in the cooler tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
111
2
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 12 publications
12
111
2
9
Order By: Relevance
“…6, 10 The wide age range of the cases in this outbreak is consistent with this pattern and similar to other tropical South-East Asia countries such as Malaysia, the Philippines and Thailand where more than 90% seroconversion can only be seen in those older than 30 years.…”
supporting
confidence: 61%
“…6, 10 The wide age range of the cases in this outbreak is consistent with this pattern and similar to other tropical South-East Asia countries such as Malaysia, the Philippines and Thailand where more than 90% seroconversion can only be seen in those older than 30 years.…”
supporting
confidence: 61%
“…Ninety-two isolates were E1 genotype strains (67 from Australia and 25 from New Zealand), 38 were genotype E2 (30 from Australia and 8 from New Zealand), 15 (Table 2). No BglI Ϫ PstI Ϫ isolates were identified in this study, although a double-negative isolate was described in an earlier study from Australia (3).…”
Section: Resultsmentioning
confidence: 99%
“…Varicella displays a marked seasonality (peaking in late winter or spring) in temperate climates, and infection is nearly ubiquitous by age 20. For reasons that remain unclear, seasonality does not occur in tropical countries, and a larger proportion of people enter adulthood uninfected by VZV (14,15). In addition, several studies have demonstrated a distinctive geographic distribution of the major VZV genotypes aligning with cool versus warm global climates (2,18,28).…”
mentioning
confidence: 99%
“…There is no previous study in this province to compare VZV prevalence in two sexes. However, no difference was found in the VZV seropositivity in other studies in Iran (5) and some other parts of the world (13)(14)(15).…”
Section: Discussionmentioning
confidence: 38%